Pedagogical Conditions of College Students’ Core Competencies Formation in the Process of Foreign Languages Learning - Maksimova, Elvira V.; Gatin, Renat G.; Nazmutdinova, Munira A.; Zorina, Anna V.; Vygodchikova, Natalya N.; Khrisanova, Elena G.; Vorobyeva, Inna V.; Dolgasheva, Mira V. (International Review of Management and Marketing, 2016)
The relevance of the problems stated in the article is conditioned by the fact that with the expansion of international economic relations and the increasing number of joint ventures and companies, there is an urgent need for specialists capable of intercultural communication for the implementation of the business contacts and contracts, the conclusion of economic agreements with foreign partners, cooperating with enterprises of different countries. In this regard, this article is aimed at identifying and studying of the pedagogical conditions of college students’ core competencies formation in the process of foreign languages learning. The article clarifies the composition of core competencies in college students’ foreign languages learning; identifies a set of criteria for selection of the content of discipline "Foreign language"; reveals the effectiveness of pedagogical technologies of college students’ core competencies formation in the foreign languages learning; provides quality monitoring technology of college students’ core competencies formation in the process of foreign languages learning. Keywords: Curriculum, Students, Foreign Languages, Core Competences. JEL Classifications: A23, I23, I26